INTRERPRETASI SENSE OF PLACE DALAM GAME CALL OF DUTY 4: MODERN WARFARE - Rengga Andhita, Pundra (El-Hamra, 2019)
Abstract: Sense of Place is related to emotional relationships born from the interaction betweenhumans and places. The game was born as a public space involving the interpretation of the ownerof the place, views or perceptions of reality outside the game. Call of Duty 4: Modern Warfareshows the existence of coherent elements of place including physical settings, images and meaningsof the game. This research shows that physical settings in the game Call of Duty 4: Modern Warfarehave strong relevance between images in real-life games outside the game. Relevance is arrangedwith excellent detail so that it makes players easier to assemble imaginations that are identical toeveryday life. The aspects of the image generated in the game Call of Duty 4: Modern Warfare arearranged very precisely through a combination of visual appearance and strong narration. Theinterpretation order in this game is inseparable from the existence of games as one of the idealcommunication channels to disseminate ideas according to the sender. The meaning formedthrough this game is an accumulation of physical settings and adequate narration according to thewill of the maker. These three things succeeded in shaping players' perceptions in the directionexpected by producers of Call of Duty 4: Modern Warfare.Key Words: call of duty, sense of place, video, games, public space